ANALISIS NOVEL “LAFAL CINTA” KARYA KURNIAWAN AL-ISYHAD MENGGUNAKAN PENDEKATAN PRAGMATIK - Angraini, Debie; Permana, Indra (IKIP Siliwangi, 2019)
The novel “Lafal Cinta” is chosen by the reader to be reviewed because the reader is interested with the religious genre chosen by the novelist and in the choice of words used in the novel. The author is able to convey messages with words that are capable of touching the reader’s heart and the story that is raised is common story in everyday life so the readers not difficult to understand the plot . The aim of the reader is to study the novel “Lafal Cinta” which is in addition to knowing the plot of the novel “Lafal Cinta” itself, readers also want to study the novel “Lafal Cinta” and realize their role as an appreciatio in appreciating, judging, and deepening a workand to know the moral message contained in the novel “Lafal Cinta”. In this case, the pragmatic approach chosen by the reader to study a literary work is in the form of a novel entitled “Lafal Cinta” by Kurniawan Al-Isyhad. The novel “Lafal Cinta” is a religious genre vovel and very interesting to read. Through this novel the reader is invited to contemplate every mistake that has been done and learn to take lessons from those mistakes and not repeat them again.